O conhecimento de si mesmo: um estudo em fenomenologia existencial a partir da prática do Aikido - Sampaio, Vitor Faustino (2013)
The research objective was to understand the meaning of self knowledgement in a existential phenomenological perspective as from an experience where the opening to self knowledge is found. We´ve chosen as an experience the practice of Aikido and the authorial reflections about it. The use of personal narrative, making the research building, became the own experience witnessing and investigation method, founded on Martin Heidegger´s hermeneutics. Questions about the self knowledgement emerged from the personal report about the author experience from he´s Aikido´s practice. We explained those questions as self caring disposal, and submitted it to a phenomenological analysis, done in three essays: The comprehension of its self as access to the way , where we explore the meaning and explain the knowledge of its self as a walking through the existence on its execution; The self knowledge and being-with , as from reflections about the others, we learn them as inseparable part of knowing its self, and we also reflect about the dwelling in the human ethos; The self knowledge and bodyhood , on this essay we discern the conception of body on the philosophical history from the conception of bodyhood for Heidegger´s Ontology. By doing so, we could think about the body (bodyhood) as fundamental for understanding the human existence. The conceptual probation we realize on these essays, allows us to understand those were the possible aspects to be accessed from the initial narrative. Such aspects we analyzed opened the reflection about the self knowledge´s theme that permeates the human existence on its everydayness, and its implications when thinking the Existential Phenomenological Clinics practices